MANFAAT AKTIVITAS FISIK UNTUK WELL BEING LANJUT USIA: LITERATURE REVIEW - Nurvitasari, Inna; Rahman, Farid (Poltekkes Kemenkes Bandung, 2024)
Background: Decreased fitness in the elderly has an impact that covers various aspects of health, including physical, mental and emotional. A decrease in the degree of fitness will lead to a decrease in physical condition that can limit daily activities in the elderly. Objectives: This study focuses on physical activities that affect the wellbeing of the elderly such as the type, intensity, and duration of physical activity. Methods: Using Scoping Review as a guideline. Studies were collected by systematically searching the Google Scholar database, NCBI, Sciencedirect and so on covering publications from 2014-2024. Results: Of the 93,806 articles identified, 15 articles were selected according to the inclusion criteria regarding the benefits of physical activity for wellbeing in the elderly and indicated the type, intensity and duration of physical activity. Conclusions: Based on the review of the 15 articles studied, it was found that the benefits of structured exercise at the level of physical activity, especially moderate intensity physical exercise, is a safe and effective way to improve fitness in the elderly.